2003
DOI: 10.1523/jneurosci.23-06-02348.2003
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Extracellular Signal-Regulated Kinase by Stretch-Induced Injury in Astrocytes Involves Extracellular ATP and P2 Purinergic Receptors

Abstract: Gliosis is characterized by hypertrophic and hyperplastic responses of astrocytes to brain injury. To determine whether injury of astrocytes produced by an in vitro model of brain trauma activates extracellular signal-regulated protein kinase (ERK), a key regulator of cellular proliferation and differentiation, astrocytes cultured on deformable SILASTIC membranes were subjected to rapid, reversible strain (stretch)-induced injury. Activation of ERK was observed 1 min after injury, was maximal from 10 to 30 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
192
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(201 citation statements)
references
References 66 publications
7
192
2
Order By: Relevance
“…ADP evokes an increase in the PI3-K activity and blocking of the P2Y 1 receptor by MRS2179 additionally increases this ADP response. These results suggest that the P2Y 1 receptor has an inhibitory effect on PI3-K signaling pathway [25] . In our study, we found that blockage of P2Y 1 receptor could increase the production of GDNF.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…ADP evokes an increase in the PI3-K activity and blocking of the P2Y 1 receptor by MRS2179 additionally increases this ADP response. These results suggest that the P2Y 1 receptor has an inhibitory effect on PI3-K signaling pathway [25] . In our study, we found that blockage of P2Y 1 receptor could increase the production of GDNF.…”
Section: Discussionmentioning
confidence: 72%
“…Inhibition of ERK signaling blocks phosphorylation of Ser727-STAT3, and inhibition of STAT3 activation prevents ATP-stimulated mitogenesis [7] . ATP released by injuried astrocytes activates ERK through P2X 2 and P2Y 1 [25] . ADP can activate ERK1/ERK2 through P2Y 1 and P2Y 12 which leads to cell proliferation of cultured glioma C6 cells [26] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Erk1/2 and p38 MAPK, the downstream signaling mechanisms triggered by shock wave-induced P2 receptor activation may also involve additional signaling intermediates such as Ras and hypoxiainducible factor 1a transactivation (20,23). A study dealing with stretch-induced injury reported the activation of Erk1/2 to be dependent on the rate and amplitude of mechanical impact, involving released ATP and activated P2 receptors (46). Akt and mammalian target of rapamycin signaling pathways are known as essential regulators of cell proliferation (50 -52).…”
Section: Discussionmentioning
confidence: 99%
“…20,57 ATP released by astrocytes activates AKT and ERK signaling, resulting in gliosis following traumatic brain injury. 58,59 Injury-triggered extracellular ATP also affects microglial response following brain injury. 60,61 We have identified that injury-triggered lysosome exocytosis causes secretion of acid sphingomyelinase (ASM), which is needed for cell membrane repair.…”
Section: Discussionmentioning
confidence: 99%